Colonizing Other Life-Supporting Planets: An Unrealistic Fantasy - Gurevitz, Michael; Dagan, Roee (European Journal of Applied Sciences, 2024)
A leap in human cognitive evolution that occurred approximately 50-65 thousand years ago led to the acquirement of linguistic abilities, which defined ever since the modern Homo sapiens.